Use Via Early Access to Ixazomib (UVEA-IXA) Study: Effectiveness and Safety of Ixazomib-based Therapy in Relapsed/Refractory Multiple Myeloma Outside of the Clinical Trial Setting - Ludwig, Heinz; Ramasamy, Karthik; Mateos, María-Victoria; Kishore, Bhuvan; Gergely, Varga; Ladicka, Miriam; Ori, Alessandra; Simoni, Lucia; Bent-Ennakhil, Nawal; Stull, Dawn Marie; Gavini, François; Terpos, Evangelos; et al. (Clinical lymphoma, myeloma & leukemia, 2024)
BACKGROUND: In multiple myeloma (MM), improving our understanding of routine clinical practice and the effectiveness of agents outside of clinical trials is important. TOURMALINE-MM1 data resulted in approval of ixazomib for MM patients who have received ≥ 1 prior therapy. PATIENTS AND METHODS: UVEA-IXA comprised a retrospective chart review in the early access program, and a prospective 1-year follow-up period. Eligible patients had had a biochemical and/or symptomatic relapse after 1-3 prior lines of therapy; no anti-MM therapy for > 3 cycles at the start of ixazomib therapy; and an Eastern Cooperative Oncology Group performance score of 0-2. Lenalidomide- or proteasome inhibitor (PI)-refractory patients were ineligible. Primary endpoints were response and progression-free survival (PFS). RESULTS: Of 357 enrolled patients, 309 were evaluable; most patients received ixazomib alongside lenalidomide (98%) and dexamethasone (97%); 61% had received 2-3 prior lines of therapy. Median PFS was 15.6 months (95% confidence interval [CI]: 12.0-20.6) in all evaluable patients, and 19.6 (95% CI: 12.1-27.0) and 13.9 (95% CI: 10.1-18.1) months in patients who received 1 and ≥ 2 prior lines of therapy, respectively. The overall response rate was 67% in all evaluable patients, and 72% and 63%, respectively, in patients who received 1 and ≥ 2 prior lines of therapy. Median overall survival was 35.5 months. The ixazomib safety profile was consistent with previous reports. CONCLUSION: This study supports ixazomib-based therapy as an effective and tolerable treatment in the real-world. Outcomes were favorable in patients with 1 or ≥ 2 prior lines of therapy who were not lenalidomide- or PI-refractory.
Keywords: glycin; Neoplasm Recurrence, Local; lenalidomid; lidé; mnohočetný myelom; Lenalidomide; Boron Compounds; Antineoplastic Combined Chemotherapy Protocols; uvea; protokoly protinádorové kombinované chemoterapie; retrospektivní studie; prospektivní studie; Uvea; Prospective Studies; dexamethason; Dexamethasone; lokální recidiva nádoru; Glycine; Multiple Myeloma; sloučeniny boru; Retrospective Studies; Humans